Estimating age‐specific influenza‐related hospitalization rates during the pandemic (H1N1) 2009 in Davidson Co, TN - Jules, Astride (Blackwell Publishing Ltd, 2012)
Please cite this paper as: Jules et al. (2012) Estimating age‐specific influenza‐related hospitalization rates during the pandemic (H1N1) 2009 in Davidson Co, TN. Influenza and Other Respiratory Viruses 6(3), e63–e71. Background  In April 2009, a pandemic caused by a novel influenza strain, the A(H1N1)pdm09 virus, started. Few age‐specific estimates of hospitalizations associated with the first year of circulation of the pandemic virus are available. Objectives  To estimate age‐specific hospitalization rates associated with laboratory‐confirmed A(H1N1)pdm09 virus in Davidson County, TN, from May 2009 to March 2010. Patients/methods  Two separate strategies were applied: capture–recapture and surveillance‐sampling methods. For the capture–recapture estimates, we linked data collected via two independent prospective population‐based surveillance systems: The Influenza Vaccine Effectiveness Network (Flu‐VE) tested consenting county patients hospitalized with respiratory symptoms at selected hospitals using real‐time reverse transcriptase polymerase chain reaction (rRT‐PCR); the Emerging Infections Program identified county patients with positive influenza tests in all area hospitals. For the surveillance‐sampling estimates, we applied the age‐specific proportions of influenza‐positive patients (from Flu‐VE) to the number of acute respiratory illness hospitalizations obtained from the Tennessee Hospital Discharge Data system. Results  With capture–recapture, we estimated 0·89 (95% CI, 0·72–1·49), 0·62 (0·42–1·11), 1·78 (0·99–3·63), and 0·76 (0·50–1·76) hospitalizations per 1000 residents aged <5, 5–17, 18–49, and ≥50 years, respectively. Surveillance‐sampling estimated rates were 0·78 (0·46–1·22), 0·32 (0·14–0·69), 0·99 (0·64–1·52), and 1·43 (0·80–2·48) hospitalizations per 1000 residents aged <5, 5–17, 18–49, and ≥50 years, respectively. In all age‐groups combined, we estimated approximately 1 influenza‐related hospitalization per 1000 residents. Conclusions  Two independent methods provided consistent results on the burden of pandemic virus in Davidson County and suggested that the overall incidence of A(H1N1)pdm09‐associated hospitalization was 1 per 1000 county residents.